Graphical plot and correlation analysis for establishing an acceptance of future intention of exclusive breastfeeding among medical and dental students: a study from Hospital Universiti Sains Malaysia - Mohamad, Noraini; Wan Ahmad, Wan Muhamad Amir; Mohd Ibrahim, Mohamad Shafiq; Aleng, Nor Azlida; Abdul Halim, Nurfadhlina; Adnan, Mohamad Nasarudin; Mohamad Ghazali, Farah Muna (Editorial Office of Journal of Coastal Life Medicine, 2023)
The objective of this research was to identify and analysethe correlation between various factors that could impact the likelihood of medical and dental students at Hospital Universiti Sains Malaysia (Hospital USM), Kelantan, Malaysia to intend to exclusively breastfeed in the future.Thequestionnaire was designed and validated. The validated questionnaire was distributed among medical dan dental students. The study involved 162 participants, comprising 25 (15.4%) students from the dental program and 137 (84.6%) from the medical program.There are56 (34.6%) male and 106 (65.4%) female involved in this study. At first, the collected data were analysedusing MINITAB software through the contour plot and surface plot. Second, the data wereanalysedusing the Spearman correlation.The result from correlation analysis shows that, most of the studied factorsrelated to general knowledge rather than other studied factors. The discovery indicates that one approach to promotingthe acceptance of exclusive breastfeeding among medical and dental students is byimproving their general knowledge about the topic. The correlation analysis, 3-D plot, and contour plot demonstrate that factors such as gender, marital status, and specific and general knowledge are associated with the intention to exclusively breastfeed in the future.This finding is very important especially for awareness education, and establishing the future exclusive breastfeeding practiced among future parents.